1998
DOI: 10.1099/0022-1317-79-11-2695
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a post-Columbian introduction of human T-cell lymphotropic virus [type I] [corrected] in Latin America.

Abstract: To investigate the origin and dissemination of human T-cell lymphotropic virus type I in Latin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0
3

Year Published

2001
2001
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 74 publications
(47 reference statements)
8
84
0
3
Order By: Relevance
“…Third, if the virus had been introduced a long time ago, it would have been more prevalent. Therefore, the African origin of the Amerindian strains is very likely and is supported by recent results providing evidence for post-Colombian introduction of HTLV-I into Latin America (Van Dooren et al, 1998).…”
Section: The Origin Of Htlv-i Infection In French Guianasupporting
confidence: 55%
“…Third, if the virus had been introduced a long time ago, it would have been more prevalent. Therefore, the African origin of the Amerindian strains is very likely and is supported by recent results providing evidence for post-Colombian introduction of HTLV-I into Latin America (Van Dooren et al, 1998).…”
Section: The Origin Of Htlv-i Infection In French Guianasupporting
confidence: 55%
“…No sera were HIV/HTLV co-infected. Although Peru harbors four different ethnic groups: the Quechuas of Inca origin, Nikkei of Japanese descent, Mestizo of mixed white-Indian, and blacks or mulattos of African origin, HTLV-1 has been detected in all groups, and a molecular clock study confirmed a post-Columbian introduction of virus in the country 27 .…”
Section: Resultsmentioning
confidence: 92%
“…The geographical origins of the strains other than those from Guyana, Suriname, and French Guiana reported in the cosmopolitan HTLV-1 subtype A are as follows, from top to bottom: PT12, PT3, and PT5, Brazil; PT1 and PT18, Caribbean; Abel2, Reunion Island; PH121, Senegal; CH, Caribbean; ARGMF, Argentina; TSP1, MEL, ATK, H5, OUL, AKR, AKE, MAP, BAT, and MT2, Japanese group; HS35, Caribbean; SIE and SIK, Ivory Coast; PH122, Senegal; and PH333, Mauritania. The sequences in the phylogenetic tree are reported elsewhere (12,13,23,24,46,49,50 closely related to the strains from French Guiana derived from Amerindians and Creoles and to some strains from Brazil.…”
Section: Resultsmentioning
confidence: 99%